(untitled) (Bangladesh Journal of Medical Science, 2013)
Aim: Cardiovascular disease is on the rise and is expected to be a leading cause of death and disability worldwide. Identification of risk in asymptomatic individual in higher risk group could help to plan individual patients management. Positive family history is one of the risk factors and screening at this level may help in determining individual therapy. Studies have shown relation of positive family history but are lacking in this part of world, so we considered it worthwhile to assess FRS in asymptomatic sibling of CAD Patients Materials and methods: 75 volunteers were enrolled in the study and they underwent Bruce treadmill exercise protocol after their initial evaluation, these volunteers than also underwent biochemical test Fasting blood sugar and lipid profile. These volunteers were divided into two groups based upon their Treadmill test results. Results: 31 out of 75 volunteers were TMT positive and they were kept in one group. These volunteers differed significantly (p<0.05) in higher age, fasting blood sugar and Low density lipoprotein level (LDL). This group also had a significantly lower metabolic equivalents and higher Framingham Risk Score. Conclusion: Our study showed that positive family history is associated with a higher Framingham risk score in asymptomatic volunteers. DOI: http://dx.doi.org/10.3329/bjms.v12i1.11825 Bangladesh Journal of Medical Science Vol. 12 No. 01 January13 pp.68-73